2015
DOI: 10.1186/s12864-015-2118-8
|View full text |Cite
|
Sign up to set email alerts
|

Time course of the response to ACTH in pig: biological and transcriptomic study

Abstract: BackgroundHPA axis plays a major role in physiological homeostasis. It is also involved in stress and adaptive response to the environment. In farm animals in general and specifically in pigs, breeding strategies have highly favored production traits such as lean growth rate, feed efficiency and prolificacy at the cost of robustness. On the hypothesis that the HPA axis could contribute to the trade-off between robustness and production traits, we have designed this experiment to explore individual variation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(37 citation statements)
references
References 60 publications
0
35
0
Order By: Relevance
“…It has been demonstrated that glucocorticoids increase the transcription of DUSP1 gene by binding to GRE region in A549 human lung adenocarcinoma cells (Shipp et al, 2010). CXCR4, IL7R, and TXNIP genes were differentially expressed in response to ACTH in pigs (Sautron et al, 2015). Fkbp5 is identified as glucocorticoid-responsive genes and is regulated by the binding GR to the sequences corresponding to the GRE in Fkbp5 gene region (U et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been demonstrated that glucocorticoids increase the transcription of DUSP1 gene by binding to GRE region in A549 human lung adenocarcinoma cells (Shipp et al, 2010). CXCR4, IL7R, and TXNIP genes were differentially expressed in response to ACTH in pigs (Sautron et al, 2015). Fkbp5 is identified as glucocorticoid-responsive genes and is regulated by the binding GR to the sequences corresponding to the GRE in Fkbp5 gene region (U et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…ACTH activated the expression of glucocorticoidresponsive genes: Five genes, namely CXCR4, DUSP1, IL7R, TXNIP, and Fkbp5, have been proposed as markers of differential regulation of glucocorticoid-responsive elements (Donn et al, 2007;Sautron et al, 2015). In order to study whether ACTH activates GR-related pathways and affects downstream gene expression, we examined the mRNA levels of these genes.…”
Section: Effect Of Acth On the Oxidant Levels And Activity Of Antioximentioning
confidence: 99%
“…Venn diagram was edited to enlighten commonalities between the lists of unique genes identified as VIP for the three traits protein family which plays a role in immune regulation and basic cellular processes involving protein folding and trafficking. In juvenile pigs, FKBP5 was proposed as a candidate gene for a better understanding of the stress response, notably due to its connexion with the glucocorticoid receptor [27]. Interestingly, it is known that FE is associated with the susceptibility to stress in cattle [28], and that RFI and cortisol response are also positively associated in rams [29].…”
Section: Discussionmentioning
confidence: 99%
“…PCA was performed with EZinfo (version 3.0.3). Multilevel PCA 14 was performed using mixOmics (version 6.1.3). Pareto scaling was used in PCA and mPCA modelling.…”
Section: Methodsmentioning
confidence: 99%